Effect of breed, diet, period and lactation numbers on immunoglobulin G concentration in swine colostrum - Neto, Raul Machado; Packer, Irineu Umberto; Menten, José Fernando; Lavorenti, Abel (Pesquisa Agropecuaria Brasileira, 2001)
The objective of the present study was to determine the effects of breed, diet, period of the year and lactation numbers on the concentration of immunoglobulin G (IgG) in sows colostrum. IgG concentration was determined in colostrum of 60 sows (33 Large White and 27 Landrace) submitted to four different diets with 0%, 7%, 14% and 21% of dried yeast. Dried yeast from alcohol of sugar cane industry (Saccharomyces cerevisiae) was used as substitute for corn and soybean mill keeping the level of crude protein at 14%. IgG concentration in the colostrum was not affected by breed and diet. Higher concentration of IgG was found in colostrum of sows farrowing occurred between May and October (P < 0.05). Quadratic (P < 0.10) and cubic (P < 0.01) effects of parturition order on IgG concentration were detected. Females from first parturition had lower concentration (P < 0.05) of IgG (49.98±7.9 mg/mL) compared to females from second (92.70±5.9 mg/mL), third (70.72±5.6 mg/mL) and fourth (85.56±9.0 mg/mL) parturition, demonstrating that animals with more immunological experience have higher concentrations of IgG in the colostrum.